Measuring for change/Mobile Creches - Vohra, Chavi; Shah, Minal; Mishra, Atishi; Gupta, Ankita (Frontiers in Public Health, 2024)
Introduction: Research spanning decades across fields like psychology, education, and neuroscience consistently highlights the crucial role of social emotional skills in various aspects of personal, academic, and professional development (Greenberg et al., 2003;Lopes et al., 2005;Durlak et al., 2011). The fact that UNESCO recognises social emotional learning (SEL) as essential not just for meeting its educational objectives but also for accomplishing the Sustainable Development Goals highlights the crucial role robust social emotional development plays in establishing sustainable societies. Whilst various studies highlight the importance of SEL, there is limited attention on how organisations can contribute to building such development by consciously including SEL in their work practice. Process/methods: Our case study presents the process of integrating SEL into organisational practice over a period of nine months. The selected constructs of SEL were determined by the organisation's needs and values. The Measurement for Change approach was used to frame and implement the intervention, with interactive discussions being the key methodology. Data was collected via surveys, reflective sharing and observations. Results: A shift on the selected constructs of SEL was recorded, with data highlighting individual differences. Conclusion: The process of co-design and continual reflective practice was key to achieving change within the subset of the organisation, rather than the specific content of the materials used. Context MC's key programmes include childcare services, both directly and through partnering with civil society organisations and the state government, enhancing community engagement, and delivering parenting programmes. Through its extensive networking with local, national, and international organisations, MC also advocates for child centered policies with the government. MC has reached out to 870,000 children, mainstreamed 100,000 children in formal schools, trained 6,500 women as childcare workers, run 800 day-care centers, partnered with over 250 builders, networked with over 100 Non-Government Organisations (NGO) and influenced key policies, laws, and programmes. Currently, MC has 150 members.In developing the programme, MC has partnered with Saving Brains, a knowledge platform of Grand Challenges Canada, and worked with subject experts. Through a series of reflective and